The involvement of a Panay-based Non-Governmental Organization (NGO) in the promotion of corporate social responsibility. - Dollosa, Viviera S.; Guillergan, Zendy Evans G. (2008.)
This study looked into the involvement of a Madia-as Ecological Movement (MEM), a panay-based environmental NGO, in the promotion of Corporate Social Responsibility (CRS). MEM dealt with Petron for the Guimaras oil spill and Mindoro Resource Limited Gold, a mining company that conducted exploration activities and proposed mining operations in Pan de Azucar Island, Concepcion. to induce CSR from the target companies, Madia-as employed an indirect usage strategy against Petron, wherein it used the government and civil society to pressure the oil company to pay for the damages brought about by the oil spill. In pursuit of its goals of stopping the exploration activities in Concepcion, MEM utilized indirect withholding strategy which involved withholding an important resource (i.e. mining exploration permit) from MRL Gold. Although Petron and MRL Gold responded to the tactics of MEM, the latter was unable to gain control over the resources needed by the target companies which would have served as leverage for MEM against Petron and MRL Gold. Consequently they were not able to manipulate power relations and compel the target companies to meet their demands.
Thesis (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo
Keywords: Non-Governmental Organization (NGO)--Madia-as Ecological Movement (MEM)